2013
DOI: 10.4012/dmj.2012-295
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of coated mannan against the adhesion of Candida biofilms to denture base resin

Abstract: The adherence of Candida on dentures is related to diseases such as denture stomatitis and aspiration pneumonia. Mannan is a major component of the Candida cell surface, and contributes to the cell adherence. A previous report indicated that the adherence of C. albicans to culture dishes was inhibited by the coating them with mannan. The purpose of this study was to examine the adhesion inhibitory effect of mannan coating on acrylic denture surfaces against C. albicans and C. glabrata. The amount of Candida at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
0
13
0
7
Order By: Relevance
“…La capa más externa de la pared celular de Candida albicans consta de un complejo de polisacáridos principalmente Manán, Glucán y Quitina, además de proteínas y una proporción variable de lípidos, los cuales están involucrados en la adhesión a las células del huésped, así como a las propiedades antigénicas (12).…”
Section: Discussionunclassified
“…La capa más externa de la pared celular de Candida albicans consta de un complejo de polisacáridos principalmente Manán, Glucán y Quitina, además de proteínas y una proporción variable de lípidos, los cuales están involucrados en la adhesión a las células del huésped, así como a las propiedades antigénicas (12).…”
Section: Discussionunclassified
“…Sato and co‐workers investigated mannan coating as an antiadhesion coating on acrylic denture surfaces against C. albicans and Candida glabrata microorganisms . Research showed that mannan inhibited the adhesion of both Candida strains in a concentration‐dependent manner.…”
Section: Applicationsmentioning
confidence: 99%
“…Os diferentes graus de inflamação palatal, que podem ocorrer como resultado do uso de próteses, são normalmente associados a presença de um grande número de micro-organismos do gênero Candida no espaço entre a mucosa que recobre o palato e a superfície da prótese [11,36,40], sendo assim as próteses funcionam como um reservatório onde estes micro-organismos se proliferam causando a infecção [43,44].…”
Section: Manifestações Clínicas Da Doençaunclassified
“…ao acrílico [42,44,45], ao fluxo de saliva reduzido sob as superfícies da prótese, à má adaptação das próteses totais, ao uso noturno e à deficiência na higiene oral [3,11,36]. As superfícies ásperas das próteses, especialmente na região que recobre o palato, tendem a favorecer o desenvolvimento do biofilme uma vez que nestas superfícies é mais difícil a eliminação de micro-organismos.…”
Section: Manifestações Clínicas Da Doençaunclassified
See 1 more Smart Citation